PENGETAHUAN IBU TENTANG GIZI DAN POLA KONSUMSI PROTEIN BERBASIS PANGAN LOKAL PADA ANAK BADUTA STUNTING : Pengetahuan Ibu tentang Gizi dan Pola Konsumsi Protein Berbasis Pangan Lokal pada Anak Baduta Stunting - Choirun Nissa, S.Gz.,M.Biomed; Ilmiatul Mustafidah; Guritan Indra Sukma (Amerta Nutrition, 2022)
Background: Stunted in under two years children have the potential to suffer a decrease in intellectual ability, productivity disorder, and an increased the risk of degenerative diseases in the future.   Objectives: This study aims to determine the relationship between maternal knowledge of nutrition and protein consumption pattern based on local food in stunted under two years children.   Methods: The design of this research is Cross Sectional. Purposive sampling method obtained 35 subjects, Maternal knowledge of nutrition is measured by using a questionnaire, protein consumption patterns is measured by using the Semi FFQ form. Spearman Product Moment Test is used to bivariate test.   Results: There is no correlation between maternal knowledge of nutrition and local food-based protein adequacy in stunted under two years children (p = 0.214 > 0.05). Further test showed that there was a significant relationship between maternal knowledge of nutrition and the frequency of protein consumption patterns based on local foods with p= 0.023 (p< 0.05) with r= 0.384.   Conclusions: Maternal knowledge of nutrition as a determinant factor that affect the frequency of animal protein consumption based on local foods in stunted under two years children.